Rotating shift work, sleep, and accidents related to sleepiness in doctors - Shravani Deolia; Kumar Gaurav Chhabra; Gargi S Nimbhorkar; Christina L Pachuau; Angel S Yangad; Gargi Nimbulkar; Sanjana S Basu (Wolters Kluwer Medknow Publications, 2021)
Background: Rotating shift work refers to a way of organizing daily working hours in which different persons or teams work in succession to cover more than the usual 8 h per day, up to and including the whole 24 h. Studies have been conducted for examining the effects of rotating shifts on an employee's performance and well-being. Hence, the aim of the present study was to evaluate the effect of rotating shift work, sleep, and accidents related to sleepiness in doctors. Methodology: A cross-sectional study was conducted on doctors of a Tertiary Care Hospital. A close-ended questionnaire containing 25 questions was distributed to doctors (residents and interns) who worked rotating shifts. Questions presented were regarding sleep disturbances, sleeping aids or countermeasures to get to sleep; and accidents or errors in the past year including automobile accidents and medical and procedural errors that the doctors had reported to have occurred because of sleepiness due to rotating shifts. The data collected were analyzed by SPSS version 21 (SPSS statistics IBM Corporation). Results: Doctors reporting to night shifts suffered from decreased and disturbed sleep, irritability, fatigue, and poor reflexes. According to our study, almost all the subjects suffered from poor work and sleep quality due to their changing work shifts. Conclusion: Rotating work shifts have a direct effect on workability and quality and amount of sleep in doctors.